Comparison of Fontan Survivors with and without Pacemakers: A Report from the Pediatric Heart Network Fontan Cross‐sectional Study. (4th July 2012) - Williams, Richard V.; Travison, Thomas; Kaltman, Jonathan R.; Cecchin, Frank; Colan, Steven D.; Idriss, Salim F.; Lu, Minmin; Margossian, Renee; Reed, John H.; Silver, Eric S.; Stephenson, Elizabeth A.; Vetter, Victoria L.; et al.
Abstract Objective. Although many Fontan patients undergo pacemaker placement, there are few studies characterizing this population. Our purpose was to compare clinical characteristics, functional status and measures of ventricular performance in Fontan patients with and without a pacemaker. Patients and Design. The National Heart, Lung, and Blood Institute funded Pediatric Heart Network Fontan Cross‐Sectional Study characterized 546 Fontan survivors. Clinical characteristics, medical history and study outcomes (Child Health Questionnaire [CHQ]), echocardiographic evaluation of ventricular function, and exercise testing) were compared between subjects with and without pacemakers. Results. Of 71 subjects with pacemakers (13%), 43/71 (61%) were in a paced rhythm at the time of study enrollment (age 11.9 ± 3.4 years). Pacemaker subjects were older at study enrollment, more likely to have single left ventricles, and taking more medications. There were no differences in age at Fontan or Fontan type between the pacemaker and no pacemaker groups. There were no differences in exercise performance between groups. CHQ physical summary scores were lower in the pacemaker subjects (39.7 ± 14.3 vs. 46.1 ± 11.2, P =.001). Ventricular ejection fraction z‐score was also lower (−1.4 ± 1.9 vs. −0.8 ± 2.0, P =.05) in pacemaker subjects. Conclusions. In our cohort of Fontan survivors, those with a pacemaker have poorer functional status and evidence of decreased ventricular systolic function compared to Fontan survivors without a pacemaker.